Becoming Jimi Hendrix : from Southern crossroads to psychedelic London, the untold story of a musical genius - Roby, Steven (African American music reference, 2010)
"Becoming Jimi Hendrix traces 'Jimmy's' early musical roots, from a harrowing, hand-to-mouth upbringing in a poverty-stricken, broken Seattle home to his early discovery of the blues to his stint as a reluctant recruit of the 101st Airborne who was magnetically drawn to the rhythm and blues scene in Nashville. As a sideman, Hendrix played with the likes of Little Richard, Ike and Tina Turner, the Isley Brothers, and Sam & Dave-- but none knew what to make of his spotlight-stealing rock guitar experimentation, the likes of which had never been heard before. From 1962 to 1966, on the rough and tumble club circuit, Hendrix learned to please a crowd, deal with racism, and navigate shady music industry characters, all while evolving his own astonishing style. Finally, in New York's Greenwich Village, two key women helped him survive, and his discovery in a tiny basement club in 1966 led to Hendrix instantly being heralded as a major act in Europe before he returned to America, appeared at the Monterey Pop Festival, and entered the pantheon of rock's greatest musicians. Becoming Jimi Hendrix is based on over one hundred interviews with those who knew Hendrix best during his lean years, more than half of whom have never spoken about him on the record. Utilizing court transcripts, FBI files, private letters, unpublished photos, and U.S. Army documents, this is the story of a young musician who overcame enormous odds, a past that drove him to outbursts of violence, and terrible professional and personal decisions that complicated his life before his untimely demise"--Provided by publisher